Management of chemotherapy-induced nausea and vomiting in patients receiving multiple-day highly or moderately emetogenic chemotherapy: role of transdermal granisetron. (August 2016) - Coluzzi, Flaminia; Mattia, Consalvo
Granisetron transdermal delivery system (GTDS) is the first 5-HT3 drug to be transdermally delivered and represents a convenient alternative to oral and intravenous antiemetics for the treatment of chemotherapy-induced nausea and vomiting. GTDS is effective and well tolerated in patients receiving multiple-day moderate-to-highly emetogenic chemotherapy. In this setting noninferiority studies showed similar efficacy when GTDS was compared with intravenous and oral granisetron and intravenous palonosetron. GTDS has shown good cardiovascular safety; however, special caution is needed in patients at risk for developing excessive QTc interval prolongation and arrhythmias. So far, GTDS has been investigated for intravenous prevention in comparison with granisetron and palonosetron; however, further prospects open the route to future clinical investigations.